Analisis Pelaksanaan Program Kampung Keluarga Berencana Dalam Meningkatkan Kesejahteraan Keluarga Di Kelurahan Air Dingin Kecamatan Bukit Raya Kota Pekanbaru (Studi Pada Kelompok Kegiatan Bina Keluarga Balita) - Justang Fariel Maulana (UIR Press, 2021)
Cases of malnutrition among children under five in Pekanbaru City still occur, because of the lack of knowledge of parents in caring for and monitoring the growth and development of children and ignorance of parents in providing nutrition to their toddlers. The purpose of this study was to analyze the implementation of the Kampung KB program in improving family welfare. The research method used in this research is quantitative descriptive, where data sources were obtained from interviews, questionnaires and documentation. Input of this activity is that the enthusiasm of Family Members towards BKB counseling activities is high and gets good responses, and there are a variety of activities carried out in an integrated manner, but sometimes not all family members and cadres can be present during the implementation of the activity, because it has its own busyness. Process of this activity, that BKB implementation has been routinely carried out. Recording and reporting of activities has also been carried out well, but in meetings / counseling conducted more focused on improving the quality and knowledge of cadres only. Output of this activity, is that the understanding of the people who take part in BKB counseling activities is more understanding about child development. However, the increase in the number of family members participating in the BKB outreach was not optimal.